Potential dividends and actual cash flows.A regional Latin American analysis (2009)
We examine the value market assigns to components of the cash flow to equity including potential dividends. We study non financial publicly traded firms from five Latin American countries. The model includes four variables: market value of equity, dividends paid, change in equity investment and change in liquid assets (potential dividends) and are regressed with actual equity value as dependent variable. Tests applied give robust results. The main conclusions: Market assigns less than one dollar to a future dollar for any of the variables studied. Potential dividends destroy value. A dollar invested in liquid assets has a negative Net Present Value and it is not zero NPV investments. We confirm the agency costs of keeping undistributed cash flows.